Pengaruh Model STAD Terhadap Hasil Belajar Bahasa Indonesia Siswa kelas V SDN Bahagia 06 Bekasi - Nidya Ningrum; Khairil Iba (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This study aims to analyze, test and find out whether or not there is an influence of the STAD model on the learning outcomes of Indonesian class V of SDN Bahagia 06 Bekasi. Metode Quasi Experimental, type Posttest-Only Control Group Design.  The study population of all students of class V. Samples numbered 57 from classes V-C and V-E. Cluster Random Sampling data retrieval techniques. The research instrument in the form of an objective consists of 40 questions tested in the V-D class, the number of students is 26.  Uji validity muse Biserial Point Correlation obtains 30 valid and 10 drops.  Uji reliability using KR-21 obtained rcount 0.883 with high reliability.  Uji normalitas use Lilliefors. Data were obtained from the control class and experiments were tested with homogeneity using fisher tests, group data were obtained.  The results of the hypothesis test t count 6.916 significant 0.05 will reject H0. The results of the study concluded that there was an influence on the STAD model on the learning outcomes of Indonesian class V of SDN Bahagia 06 Bekasi.